Association Between Symptom Burden at Initiation of a Graduated Return to Activity Protocol and Time to Return to Unrestricted Activity After Concussion in Service Academy Cadets. Issue 3 (March 2022) - Aderman, Michael J.; Brett, Benjamin L.; Malvasi, Steven R.; McGinty, Gerald; Jackson, Jonathan C.; Svoboda, Steven J.; McCrea, Michael; Broglio, Steven P.; McAllister, Thomas W.; Pasquina, Paul F.; Cameron, Kenneth L.; Houston, Megan N.
Background: Current consensus and position statements recommend that concussed patients be asymptomatic upon the initiation of the graduated return to activity (RTA) protocol. However, a significant number of concussed patients are beginning their RTA protocols while endorsing symptoms. Purpose: To characterize symptom endorsement at the beginning of the RTA protocol and examine the association between symptom endorsement and RTA protocol duration in service academy cadets. Study Design: Cohort study; Level of evidence, 2. Methods: A prospective cohort study was conducted with cadets at 3 US service academies. Postconcussion symptom inventories were recorded upon the initiation of an RTA protocol. The Sport Concussion Assessment Tool Symptom Inventory was used to classify participants into 3 groups (0 symptoms, 1 symptom, and ≥2 symptoms) upon the initiation of the RTA protocol. The primary outcome of interest was RTA protocol duration. Kaplan-Meier survival estimates were calculated to estimate RTA protocol duration by symptom endorsement, sex, varsity status, academic break, and time to graduated RTA initiation. Univariate and multivariable Cox proportional hazards models were used to estimate the association between symptom endorsement at the initiation of the RTA protocol and RTA protocol duration (α < .05). Results: Data were analyzed from 966 concussed cadets (36% women). Headache (42%) and faintness/dizziness (44%) were the most commonly endorsed symptoms on the Sport Concussion Assessment Tool-Third Edition and the Brief Symptom Inventory-18, respectively. Univariate results revealed a significant association between endorsing ≥2 symptoms and RTA protocol duration. In the multivariable model, endorsing ≥2 symptoms maintained a statistically significant association with RTA protocol duration. Significant associations were observed between RTA protocol duration and nonvarsity status (27% longer), women (15% longer), academic breaks (70% longer), and time to the initiation of the RTA protocol (1.1% longer daily incremental increase) after controlling for covariates. Conclusion: Symptom endorsement at the initiation of an RTA protocol was associated with RTA protocol duration. Cadets who had returned to preinjury baseline symptom burden or improved from baseline symptom burden and endorsed ≥2 symptoms at the initiation of the RTA protocol took longer to RTA.